Bioleft: a collaborative, open source seed breeding initiative for sustainable agriculture - Marin, Anabel (2021)
This chapter provides a chronological and thematic account of the work carried out in Argentina, reflecting on the lessons these experiences bring to sustainability transformations and some of the concepts covered in the earlier chapters. It describes the identification and framing of the sustainability challenge and the ways in which various methods (for example, Q-method) and transdisciplinary approaches were applied. The chapter outlines key moments in the transformation laboratory (T-Lab) process, leading to the initiation of the ‘Bioleft’ open-source seed platform, and the lessons that were learnt as a result. The ways in which the transdisciplinary team worked together and the importance of shared ownership of this pioneering model for open-source seeds as a ‘bridging innovation’ are seen as particularly important. The chapter offers specific insights from the Argentinean case.